Analisa Hosting Capacity Photovoltaic pada Feeder Adinegoro 20 kV, Kota Padang - Indora, Muhammad Fachreyza; Adrianti, Adrianti; Nasir, Muhammad; Nofendra, Riko (Universitas Sultan Ageng Tirtayasa, 2024)
Installation of PV capacity that exceeds the demand of the distribution system can produce large currents that exceed the thermal rating of the electrical components and can cause export power to high voltage levels. Therefore, the purpose of this study is to obtain the PV hosting capacity of the Adinegoro feeder and to determine the voltage profile and power loss after installation of the PV. The research method is using power flow simulation with ETAP 12.6. The PV hosting capacity calculations of the Adinegoro feeder are carried out in six locations, i.e. five locations on the secondary network and one location on the primary network. The PV capacities are continuously increased until the receiving power from the grid reaches zero or no export power from the lower voltage level to higher voltage level. From the simulation results, it is obtained that the PV hosting capacity on secondary networks, is equal to 100% of the local load. While for the primary network, the maximum PV hosting capacity is 4400 kW. The installation of PV to the Adinegoro feeder can increase the voltage profile and reduce power losses in the system.